Extraordinary properties of mechanical metamaterials fabricated by projection microstereolithography - Hu, Jingdan (Nanyang Technological University, 2023)
The need for high-performance and lightweight materials which have superior mechanical performance has continuously grown over the past few decades. The lattice structures are intriguing and perfect for cutting-edge engineering applications because of their potentially great mechanical performance and customizable low density. However, the development of complex structure has always been severely constrained by manufacturing technology. The development and quick growth of additive manufacturing has helped in the study of lattice structures and allowed for thorough and in-depth examinations of them. Simple Cubic (SC) plate lattice is of tremendous interest and relevance in the investigation of its prospective applications since it is thought to have reached the theoretical limit of mechanical performance in nanoscale. In this work, the carefully-designed cubic plate lattices were printed using the projection micro-stereolithography (PµSL) additive manufacturing technology. The effects of resin materials and geometrical factors on mechanical performance were then thoroughly examined. The results show that increasing the number of cells in the cubic plate lattice can result in a superior improvement in the compressive strength and energy absorption, displaying typical mechanical properties of metamaterials. Remarkably, these polymeric plate lattices can even exceed stainless steel lattices and some other current polymeric lattices in terms of specific energy absorption, demonstrating their wide range of possible uses in situations when high energy absorption, high strength, and light weight are required. In addition to the geometry study, properties of three different kinds of 3D printable resin materials were also explored. Their curing behaviors, structural changes, compression properties and thermal performance were also examined and tested using characterization methods. Our findings suggest that these resins exhibit various but excellent performances, such as high thermal decomposition temperature, high char yield, enhanced mechanical performance after heat treatment and so on, therefore, they meet applications for different mechanical property requirements.